2019
DOI: 10.1101/634352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Jumping To Conclusions, General Intelligence, And Psychosis Liability: Findings From The Multi-Centre EU-GEI Case-Control Study

Abstract: AbstractBackgroundThe “jumping to conclusions” (JTC) bias is associated with both psychosis and general cognition but their relationship is unclear. In this study, we set out to clarify the relationship between the JTC bias, IQ, psychosis and polygenic liability to schizophrenia and IQ.Methods817 FEP patients and 1294 population-based controls completed assessments of general intel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…Our results suggest that at least one of these questions can plausibly be answered in the affirmative, consistent with previous findings about the role of cognitive style 12 , or what the PDI is measuring 49 , or the role of a general cognitive-ability pathway even in clinical patients 50 .…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggest that at least one of these questions can plausibly be answered in the affirmative, consistent with previous findings about the role of cognitive style 12 , or what the PDI is measuring 49 , or the role of a general cognitive-ability pathway even in clinical patients 50 .…”
Section: Discussionsupporting
confidence: 91%
“…Here, a study found that participants displaying delusional psychopathology reach their conclusion on the basis of less evidence than control participants (Henquet 2020). Other recent research suggests that the JTC reasoning bias in psychosis might not be a specific cognitive deficit but rather a manifestation, or consequence, of general cognitive impairment (Tripoli 2020). This notion of patients with a delusional thought process having other more widespread abnormalities in information processing and decisionmaking is important because a patient's cognitive deficits may be more pervasive than their delusion (s).…”
Section: Cognitive Process-based Modelsmentioning
confidence: 53%
“…The effect of subjective difficulty on task performance is hard to predict. Some studies point to the possibility that low intelligence and neurocognitive deficits foster hasty decision-making (Takeda et al, 2018;Tripoli et al, 2019), especially in more difficult tasks (Gaweda et al, 2017), while other research from the field of memory suggests that difficult tasks may lead to more cautious responses in patients; the lowered confidence found here speaks for the latter (Moritz et al, 2015a). In this case, the high ambiguity (i.e., the sequence did not clearly favor one color) may have persuaded controls to decide prematurely.…”
Section: Discussionmentioning
confidence: 69%